Otolaryngology training programs: Resident and faculty perception of the mentorship experience. (11th March 2013) - Lin, Sandra Y.; Laeeq, Kulsoom; Malik, Adeel; Varela, David A. Diaz Voss; Rhee, John S.; Pillsbury, Harold C.; Bhatti, Nasir I.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The purpose of this study is to compare faculty and trainees' perceptions of their mentorship experience in otolaryngology training programs in order to identify areas where improvements could yield more productive mentorship. Study Design Cross‐sectional survey design. Methods Residents and faculty from three otolaryngology–head and neck surgery programs were surveyed regarding their perceptions of their mentoring relationship. Trainees were asked about the characteristics of their mentorship experience. Separately, faculty were asked to describe their mentorship relationship, available resources to provide effective mentorship, and to identify areas in which formal training would improve their mentoring skills. Results Forty‐eight trainees (72%) and sixty‐one faculty members (73%) completed the survey. Ninety percent of residents meet with their mentors at least twice a year. Faculty and residents (> 80%) agreed that career planning was the most commonly addressed topic in mentorship sessions. However, faculty and residents differed in their perceptions of providing mentorship in other areas including clinical judgment (P = 0.003). The majority of faculty (56%) felt that formal mentorship training would improve their mentorship skills. While 95% of mentees agreed that their mentor is accessible, only 46% of faculty believed they have enough time to dedicate to mentoring (P < 0.001). Conclusions Mentees are generally satisfied with the mentoring they receive, while most mentors are not satisfied with the time they have to provide mentorship. Further insights into differences in faculty and trainee perceptions may improve the mentorship experience. Level of Evidence 4. Laryngoscope, 123:1876–1883, 2013